MANAJEMEN PENGELOLAAN ZAKAT DAN SHADAQAH (Kiat Badan Amil Zakat Jawa Timur Dalam Mobilisasi dan Pendistribusian) - Kasno Sudaryanto (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2013)
During this time, zakat and its management just ideal in level of discourse and theory, while the realization is always constrained by two things: the synchronization of management of zakat which is still partially addressed institutional and the distribution of zakat overlap between agencies. This has led to the potential for a national charity - in the range of Rp. 217 trillion to Rp eventually absorbed only Rp. 1.7 trillion. Given this reality, East Java BAZ strives to formulate and implement measures that are considered able to eliminate or at least to minimize—the effects of 2 problems above. The initial thing to do is optimize the strategic plan through the actualization of the vision and mission of BAZ Java that is focused on optimizing the distribution of ZIS in order to realize the mandate of Law Number 38 of 1999 Jo. Law No. 23 of 2011 on Zakat. Various forms of innovation regarding methods of distribution and ZIS revenue optimization continue to be encouraged and realized, with the ultimate goal of successful realization of zakat management function effectively and efficiently, for the welfare of the people and regional poverty reduction.